2022
DOI: 10.1111/ajt.16840
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in mortality among solid organ transplant recipients hospitalized for COVID-19 during the course of the pandemic

Abstract: Mortality among patients hospitalized for COVID‐19 has declined over the course of the pandemic. Mortality trends specifically in solid organ transplant recipients (SOTR) are unknown. Using data from a multicenter registry of SOTR hospitalized for COVID‐19, we compared 28‐day mortality between early 2020 (March 1, 2020–June 19, 2020) and late 2020 (June 20, 2020–December 31, 2020). Multivariable logistic regression was used to assess comorbidity‐adjusted mortality. Time period of diagnosis was available for 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 29 publications
7
72
2
4
Order By: Relevance
“…19 Additionally, mortality from COVID-19 vaccine breakthrough infection in SOTR appears to be lower than mortality estimates among SOTR hospitalized for COVID- ). 20 This is consistent with the data from the general population which also found a lower frequency of critical COVID-19 in fully vaccinated individuals with breakthrough COVID-19 infection in comparison to unvaccinated cases (20% vs. 33.6%). 21 Unlike other groups that found a lower frequency of hospitalization in fully vaccinated individuals with COVID-19 than partially vaccinated individuals 22,23 we did not observe significant differences between our fully and partially vaccinated groups.…”
Section: Resultssupporting
confidence: 91%
“…19 Additionally, mortality from COVID-19 vaccine breakthrough infection in SOTR appears to be lower than mortality estimates among SOTR hospitalized for COVID- ). 20 This is consistent with the data from the general population which also found a lower frequency of critical COVID-19 in fully vaccinated individuals with breakthrough COVID-19 infection in comparison to unvaccinated cases (20% vs. 33.6%). 21 Unlike other groups that found a lower frequency of hospitalization in fully vaccinated individuals with COVID-19 than partially vaccinated individuals 22,23 we did not observe significant differences between our fully and partially vaccinated groups.…”
Section: Resultssupporting
confidence: 91%
“…Maintenance immunosuppression was tapered in KTR hospitalized for symptomatic COVID-19, particularly antimetabolites and mTOR inhibitors, which were discontinued in the majority of patients of both pandemic waves ( Figure 2A ). However, if modifications of maintenance immunosuppression did not differ in nature between the two waves, they were made in a smaller proportion of patients during the second wave, particularly regarding withdrawal of CNI (32.1% vs 16.6%, p<0.001) and of antimetabolites (73.7% vs 58.4%, p<0.001; Figure 2A ), which is in line with a previous report from the USA 28 . Contrasting with the global stability of immunosuppression management, anti-SARS-CoV-2 therapies differed in many respects between the two waves ( Figure 2B ).…”
Section: Resultssupporting
confidence: 90%
“…Our findings concur with a meta-analysis including 5559 KTR with COVID-19 that reported a mean mortality rate of 23% (similar to what we observed) without significant difference between “early” (studies submitted before July 2020) and “late” (studies submitted from July 2020 onwards) phases of the pandemic 43 . These conclusions conflict with a recent study showing a better prognosis in “late” (from June 20 to December 31, 2020) compared to “early” 2020 (from March 1 to June 19, 2020) among 973 solid organ transplant recipients (SOTR) hospitalized in USA for COVID-19 28 . In their report, crude mortality by 28 days indeed declined from 19.6% in early period to 13.7% in late period and after adjusting for differences in baseline comorbidities between both periods, the odds of death remained lower in the late period (aOR 0.67, 95% CI 0.46 – 0.98, p = 0 .…”
Section: Discussionmentioning
confidence: 76%
“…A number of studies have confirmed that immunocompromised patients are at high risk of developing severe COVID-19 disease and of dying when infected with SARS-CoV-2 (65)(66)(67)(68). This seems to be particularly the case in patients with combined defects of B and T cell immunity as observed early after transplantation as well as in patients given intensive chemotherapy (69)(70)(71)(72)(73).…”
Section: Immune Response To Sars-cov-2 Mrna Vaccination In Immunocomp...mentioning
confidence: 93%